The Influence Of Online Supervision Via Videoconferencing On Postgraduate Students’ Problem Understanding And Reflective Learning For Better Engagement - Nasser S, Alshahrani Amer (2021)
Video conferencing has become an important tool in education. With the help of video conferencing, education can be provided to everyone all over the globe. This technology helps to bridge the gap between students and supervisors present in different geographical places. Video conferencing tool is also being used in Saudi Arabia and is considered to be vital part of distance education being provided in the country but even after all these years, the students are having difficulties while communicating with their supervisors. This is also because of lack of proper interaction and participation process present in the education sector. Therefore, the main aim of this research is to explore the influence of online supervision via video conferencing on students’ problem understanding and reflective learning for better engagement. In order to achieve this aim, the following objectives were constructed: 1) to assess the influence of online supervision via video conferencing in terms of perceived flexibility, interaction, functional benefits, and control on postgraduate students’ problem understanding and reflective learning, 2) to evaluate the influence of personal experience in terms of students’ reflective learning and problem understanding on their online engagement, and 3) to understand the university students' perception towards the effectiveness of the videoconferencing tool for supervision purposes. A mixed method approach was adopted for this study where online survey was utilized. A total of 252 postgraduate students from three colleges in the King Saud University participated in this survey. Meanwhile, for the qualitative part, a semi structured interview method was conducted on 15 selected postgraduates’ students, in which the thematic method of data analysis was applied.